Analisis Minat Belajar Matematika ditinjau dari Lingkungan Belajar siswa kelas IX SMP - Widi Anggraini; Hasanuddin Hasanuddin (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to analyze students’ interest in learning mathematics in relation to the learning environment among ninth-grade students at SMP Negeri 03 Siak Hulu. This study employed a quantitative approach using a descriptive research design. The sampling technique used was saturated sampling, in which the entire population of 120 students was included as the research sample. Data were collected using a questionnaire developed based on indicators of learning interest and learning environment and distributed online via Google Forms. The data were analyzed using a Likert scale to determine the percentage level of students’ learning interest. The results showed that students’ interest in learning mathematics was categorized as high, with a percentage of 80.65%. This finding indicates that students demonstrated a strong level of interest, attention, and engagement in the mathematics learning process. In addition, the learning environment, including the school, family, and community environments, made a significant contribution to students’ learning interest. Therefore, a conducive learning environment needs to be continuously developed to support the improvement of students’ interest in learning mathematics.